2016
DOI: 10.1007/s10903-016-0413-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Discrimination and Cardiovascular Health Among Asian Indians in the United States

Abstract: Asian Indians (AI) have a high risk of atherosclerotic cardiovascular disease. The study investigated associations between discrimination and (1) cardiovascular risk and (2) self-rated health among AI. Higher discrimination scores were hypothesized to relate to a higher cardiovascular risk score (CRS) and poorer self-rated health. Asian Indians (n = 757) recruited between 2010 and 2013 answered discrimination and self-reported health questions. The CRS (0–8 points) included body-mass index, systolic blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The low prevalence of ideal CVH metrics in US South Asians is similar to what has been found in the general US population Longitudinal follow-up of the MASALA cohort will allow further study of the relationship between the AHA CVH metrics and progression of subclinical atherosclerosis, incident CVD events, and mortality. Effective primordial and primary prevention interventions are needed to preserve and improve CVH in US South Asians, as well as continued research on novel and emerging risk factors (Bharmal et al, 2016; Flowers et al, 2015; Nadimpalli et al, 2016; A. D. Shah et al, 2016; B.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence of ideal CVH metrics in US South Asians is similar to what has been found in the general US population Longitudinal follow-up of the MASALA cohort will allow further study of the relationship between the AHA CVH metrics and progression of subclinical atherosclerosis, incident CVD events, and mortality. Effective primordial and primary prevention interventions are needed to preserve and improve CVH in US South Asians, as well as continued research on novel and emerging risk factors (Bharmal et al, 2016; Flowers et al, 2015; Nadimpalli et al, 2016; A. D. Shah et al, 2016; B.…”
Section: Discussionmentioning
confidence: 99%
“…The issues arising from the model minority label result in undue academic pressure in SA youth and a hesitation in seeking academic help which has far reaching mental health consequences (Daga & Raval, 2018). Perceived discrimination was found to be significantly related to psychological stress for first- and second-generation SAA (Kaduvettoor-Davidson & Inman, 2013) and impacted self-reported health (Nadimpalli et al, 2016). Benner et al (2018) showed the pernicious effects of racial/ethnic discrimination across multiple domains on adolescents’ mental health, their engagement in risky health behaviors and their educational success.…”
Section: Clinical Challengementioning
confidence: 99%
“…South Asians are among the fastest growing ethnic groups in the United States (U.S.), yet epidemiological research among this group is scant (Kanaya et al, 2013;United States Census Bureau, 2010). Given higher rates of social discrimination and physical health problems experienced by South Asians, mental and physical health in this population are important spheres of study (Nadimpalli, Dulin-Keita, Salas, Kanaya, & Kandula, 2016). Within the psychosocial domain, religiosity and spirituality (R/S) are understudied constructs that may affect health outcomes.…”
Section: Introductionmentioning
confidence: 99%